The Crosstalk Between miRNA and Mammalian Circadian Clock - Wang, Xia; Tian, Guihua; Li, Zhongfeng; Zheng, Lei (Current Medicinal Chemistry, 2015)
Circadian clocks are present in most organisms to coordinate daily rhythms in physiology and behavior. The general molecular mechanisms are based on interlocked transcription-translation feedback loops driving rhythms in gene expression of a series of core clock genes. Multiple levels of regulations including transcriptional, posttranscriptional and post-translational mechanisms make circadian clock regulation more complex than once thought. Particularly, accumulating evidences have shown that miRNAs are significant players in regulating various aspects of circadian clock function. In this review, we will summarize the recent findings in the interplay of miRNAs and mammalian circadian clock and discuss future perspectives for research on the role of miRNAs played in circadian timing in health and disease.
Keywords: circadian dynamics